Optimization of GTAW Al 3003 weld using fabricated nanocomposite filler metal. Issue 3 (17th February 2019) - Ramkumar, K.R.; Natarajan, S.
ABSTRACT: Novel Al–3 wt.% TiO2 (fillers) nanocomposite has been successfully fabricated by accumulative roll bonding method to join Al 3003 alloy with the parameters of gas tungsten arc welding process such as the shielding gas flow rate (G), the welding speed (S), and the current (I) identified by response surface methodology. After preparation of weldment, studies involving X-ray diffraction and advanced electron microscopy techniques (scanning electron microscope and transmission electron microscope) have been carried out. FESEM has revealed the presence of second-phase hard ceramic particles which are embedded homogeneously in the matrix material. Energy dispersive spectroscopy analysis indicates the absence of foreign particles other than Al, Ti, and oxides. Further, the results show that the increase in mechanical properties (hardness and ultimate tensile strength) of the weldment is due to grain refinement and uniform distribution of TiO2 nanoparticles. The analysis of variance test identified the welding speed as a significant parameter on the homogeneous distribution of TiO2 particles followed by current and gas flow rate in sequential order.